Plasmepsin X activates the PCRCR complex of Plasmodium falciparum by processing PfRh5 for erythrocyte invasion - Triglia, Tony; Scally, Stephen W.; Seager, Benjamin A.; Pasternak, Michał; Dagley, Laura F.; Cowman, Alan F. (Nature communications, 2023)
Plasmodium falciparum causes the most severe form of malaria in humans. The protozoan parasite develops within erythrocytes to mature schizonts, that contain more than 16 merozoites, which egress and invade fresh erythrocytes. The aspartic protease plasmepsin X (PMX), processes proteins and proteases essential for merozoite egress from the schizont and invasion of the host erythrocyte, including the leading vaccine candidate PfRh5. PfRh5 is anchored to the merozoite surface through a 5-membered complex (PCRCR), consisting of Plasmodium thrombospondin-related apical merozoite protein, cysteine-rich small secreted protein, Rh5-interacting protein and cysteine-rich protective antigen. Here, we show that PCRCR is processed by PMX in micronemes to remove the N-terminal prodomain of PhRh5 and this activates the function of the complex unmasking a form that can bind basigin on the erythrocyte membrane and mediate merozoite invasion. The ability to activate PCRCR at a specific time in merozoite invasion most likely masks potential deleterious effects of its function until they are required. These results provide an important understanding of the essential role of PMX and the fine regulation of PCRCR function in P. falciparum biology. Plasmodium falciparum is known to secrete an aspartic protease called plasmepsin X. Here, Triglia et al present a characterisation of plasmepsin X function in the context of erythrocyte invasion and its regulation of PCRCR, a complex that anchors the leading vaccine candidate PfRh5 to the parasite surface.